From insights to action: Enriching the clinical and translational research workforce by developing diverse and inclusive career programs. Issue 1 (1st August 2022) - Ruiz, Raquel; Vitale, Alfred; Schwartz, Ann; Ossip, Deborah; Zand, Martin S.; Dozier, Ann; Egede, Leonard E.
Abstract: Diversification of the Translational Science workforce is a strategic goal for the National Center for the Advancement of Translational Science (NCATS) program. NCATS has identified the development of translational science education, training, and support for a diverse translational science workforce as key to advancing the growing field of translational science. An annual mixed-methods assessment has been conducted on Common Metrics data submitted by over 60 Clinical & Translational Science Awards (CTSA) programs nationwide and includes metrics addressing recruitment and retention of scientists with particular attention to underrepresented persons and women. This article describes a methodology for the development of From Insights to Action, a resource for guiding program implementation and strategic planning to develop a diverse clinical and translational science workforce. This was informed by the Common Metrics Initiative process and constituted of findings from qualitative interviews of a subset of CTSAs that participated. The dissemination of this guide had several impacts, including providing structural foci for the CTSA Fall 2020 program meeting centered on Diversity, Equity, and Inclusion in translational science; addressing NCATS' goal of workforce diversity; and understanding the number of diverse graduates still engaged in research.